The Turkish adaptation and psychometric properties of the Geriatric Anxiety Scale - Faika Sanal Karahan; Erdal Hamarta; Ali Yavuz Karahan (Mental Illness)
The purpose of the present study is to translate and adapt the Geriatric Anxiety Scale (GAS), a 30-item self-report measure of anxiety among older adults, into Turkish and examine its basic psychometric properties. We tested the translated GAS in a sample of community-dwelling older adults in Konya, Turkey (N=100; Mage=71.4 years, SD=6.5; range=65-88) without a history of mental disorder and sufficient cognitive abilities. To assess the convergent validity, Turkish versions of the Beck Anxiety Inventory (BAI) and Geriatric Depression Scale (GDS) were administered. The mean GAS total score was 13.33 (SD=11.86). Due to low item-total correlations (<0.30), two items (items 2 and 3) were removed from the Turkish version of the GAS. The internal reliability (Cronbach’s alpha) was excellent for the total score (0.91) and acceptable for the subscales (somatic = 0.71; cognitive = 0.85; affective = 0.84). Regarding the convergent validity, the GAS total score was significantly and positively correlated with the total scores of the BAI (r=0.87, P<0.05) and GDS (r=0.57, P<0.05), with large effect sizes. Implications: The newly translated Turkish version of the GAS has promising utility in an older adult Turkish sample. Future studies of this measure are warranted.